2021
DOI: 10.1101/2021.04.13.21255438
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

NSAID use and clinical outcomes in COVID-19 patients: A 38-center retrospective cohort study

Abstract: BACKGROUND Cyclooxygenase (COX) inhibitors including non-steroidal anti-inflammatory drugs (NSAIDs) are commonly used to reduce pain, fever, and inflammation but have been associated with complications in community acquired pneumonia and other respiratory tract infections (RTIs). Conclusive data are not available about potential beneficial or adverse effects of COX inhibitors on COVID-19 patients. METHODS We conducted a retrospective, multi-center observational study by leveraging the harmonized, high-granular… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…Two papers mentioning reviews in the title were identified: one related to ibuprofen and acute bacterial or viral respiratory lower tract infections [6], while the other was a narrative review of the issues involved [7]. We found no other systematic reviews on this topic, while some papers of potential interest provided no usable data [8,9]. In ClinicalTrials.gov, 22 studies cited COVID and NSAIDs, a few of which might be of interest when completed or published, i.e.…”
Section: Literature Searchmentioning
confidence: 99%
“…Two papers mentioning reviews in the title were identified: one related to ibuprofen and acute bacterial or viral respiratory lower tract infections [6], while the other was a narrative review of the issues involved [7]. We found no other systematic reviews on this topic, while some papers of potential interest provided no usable data [8,9]. In ClinicalTrials.gov, 22 studies cited COVID and NSAIDs, a few of which might be of interest when completed or published, i.e.…”
Section: Literature Searchmentioning
confidence: 99%
“…Thus, the use of NSAIDs in the COVID-19 setting may delay in diagnosis of SARS-CoV-2 infection due to their antipyretic principle. However, treatment with selective COX-2 inhibitors (diclofenac, meloxicam, and celecoxib) was not found to be associated with an increase in COVID-19 severity [66]. Thus, it may be said that the effects of NSAIDs represent drug-specific risk profiles in the COVID-19 setting, and it is not worthy to mention their effects in a generalized way under a single class.…”
Section: Challenges With Anti-rheumatic Agents In the Covid-19 Settingmentioning
confidence: 99%
“…The French Society of Pharmacology and Therapeutics recommended that the use of NSAIDs be avoided for symptomatic treatment in non-severe COVID-19 cases [65]. In a recent retrospective multicentre observational study, non-selective COX inhibitors (aspirin and acetaminophen) were found to be associated with increased severity and mortality in COVID-19 patients including patients with pre-existing arthritis [66]. Fever is regarded as one of the indications of SARS-CoV-2 infection.…”
Section: Challenges With Anti-rheumatic Agents In the Covid-19 Settingmentioning
confidence: 99%
“…A large retrospective study showed that use of COX inhibitors (aspirin, ibuprofen, naproxen, ketorolac) or paracetamol was significantly associated with more severe Covid-19 but only aspirin and paracetamol were associated with increased mortality (Reese et al, 2021). Another study found no effect on mortality with aspirin or NSAIDS but did find an increase in the combined endpoint of MI, stroke or venous thromboembolism (Sahai et al, 2020).…”
Section: Targeting Platelets In Covid-19mentioning
confidence: 99%